Aggregate Consumption Expenditure Function In Islamic Perspective - Imam Wahyudhi (JOURNAL OF SHARIA ECONOMICS, 2023)
Without consumption, humans will not be able to live because humans have primary needs that must be met, such as eating, drinking, and clothing. These needs are needs that must be met by humans. This research is based on literature study, exploration based on theoretical findings. the explanation of the discussion will refer to theories that are able to answer the topic of writing. references used recent published articles and supporting reference books.. The function of aggregate spending in an Islamic perspective is the belief in the existence of the Day of Judgment and the hereafter, this principle directs consumers to prefer consumption in the hereafter. Prioritizing consumption in worship rather than secular consumption. Expenditure for worship is future consumption (because in the hereafter is the reward of heaven), while worldly consumption is current consumption. The concept of the success of a Muslim's life is measured by Islamic religious morals, not by the amount of wealth. The higher the spirit, the greater the success achieved. Virtue, truth and devotion to God are the keys to Islamic morality. Virtue and righteousness can be attained by good and useful conduct and by shunning evil. A position of wealth is a gift from God, not something inherently bad (so too much is to be avoided). Wealth is a means to the end of life, if it is cultivated and used properly.